Implementasi Standar Pelayanan Penumpang Transportasi Laut di Pelabuhan Speed Boad Loleo Rute Loleo –Tidore Pada Dinas Perhubungan Kota Tidore Kepulauan - Fitriyanti Yasin; Abdul Wahid Kamma; Ilfan Baharuddin (Peneliti.net, 2023)
This research was conducted at the Tidore Islands City Transportation Service Office which aims to implement Sea Transportation Passenger Service Standards at the Loleo-Tidore SpeedBoad Port for the Loleo-Tidore Route at the Tidore Islands City Transportation Service and the constraints in implementing passenger service standards. The method used in this study is a qualitative method with a descriptive approach while data collection techniques are carried out through observation, interviews, and documentation. The results of the study indicate that the implementation of sea transportation passenger service standards at the port of Loleo has carried out a large-scale rehabilitation to meet passenger service standards. It can be seen that each passenger in a year can reach 32,361 incoming passengers and 42,428 outgoing passengers. It is better if the Department of Transportation pays more attention to existing infrastructure facilities at the Loleo speedboat port in order to make it easier for passengers to use existing facilities.